Answer:
Option (1)
Step-by-step explanation:
x -2 -1 0 1 2
y 10 2.5 0 2.5 3.0
Ist difference,
![d_1=y_2-y_1](https://tex.z-dn.net/?f=d_1%3Dy_2-y_1)
![=2.5-10=-7.5](https://tex.z-dn.net/?f=%3D2.5-10%3D-7.5)
![d_2=y_3-y_2](https://tex.z-dn.net/?f=d_2%3Dy_3-y_2)
![=0-2.5](https://tex.z-dn.net/?f=%3D0-2.5)
= -2.5
![d_3=y_4-y_3](https://tex.z-dn.net/?f=d_3%3Dy_4-y_3)
![=2.5-0](https://tex.z-dn.net/?f=%3D2.5-0)
= 2.5
![d_4=y_5-y_4](https://tex.z-dn.net/?f=d_4%3Dy_5-y_4)
![=10.0-2.5](https://tex.z-dn.net/?f=%3D10.0-2.5)
= 7.5
2nd difference,
![x_1=d_2-d_1](https://tex.z-dn.net/?f=x_1%3Dd_2-d_1)
![=-2.5+7.5](https://tex.z-dn.net/?f=%3D-2.5%2B7.5)
= 5
![x_2=d_3-d_2](https://tex.z-dn.net/?f=x_2%3Dd_3-d_2)
![=2.5+2.5](https://tex.z-dn.net/?f=%3D2.5%2B2.5)
= 5
![x_3=d_4-d_3](https://tex.z-dn.net/?f=x_3%3Dd_4-d_3)
![=7.5-2.5](https://tex.z-dn.net/?f=%3D7.5-2.5)
= 5
Since 2nd difference is common, given table represents a quadratic equation.
Let the equation is,
y = ax²+ bx + c
For a point (0, 0) passing through the quadratic equation,
0 = c
Therefore, quadratic equation is y = ax² + bx
Since ordered pair (-1, 2.5) passes through the graph of the function,
2.5 = a(-1)² + b(-1)
a - b = 2.5 ------(1)
For another point (1, 2.5)
2.5 = a(1)² + b(1)
a + b = 2.5 ------(2)
By adding equations (1) and (2),
2a = 5
a = 2.5
and from equation (2)→ y = 0
Therefore, equation of the quadratic function given in the table is y = 2.5x²
Option (1) is the answer.